The Analgesic Effect of Pineapple Fruit Juice on Mice - binti Hilmi, Ainul Atiqah; Yunivita KD, Vycke; Sadeli, Henny Anggraini (Althea Medical Journal, 2014)
Background: Pain is a feeling stimulated by the nervous system whichÂ can be suppressed by giving an analgesic agent. Some studies revealed that pineapples have an analgesic effect. This study aim was to determine analgesic effect of pineapple on mice.Methods: In this experimental study, the effect was examined by using a writhing method on the 28 male mice. Subjects were divided into 4 groups with 7 mice each. The control group received aquades and other groups received pineapple fruit juice with 20%, 40% and 80% concentration with the dosage of 10 mL/kg/body weight. After 30 minutes, 3% acetic acid was injected intraperitoneally to induce pain. Writhing responseswere observed every 5 minutes for 30 minutes.Results: The result for mean of total writhing reaction wasÂ 2.39Â±0.40, 1.92Â±0.40, 1.50Â±2.13, 1.66Â±0.11 respectively for group 1 to 4. These data indicated a significant decrease of total writhing response in mice with 20%, 40% and 80% concentration compared to control group (p=0.023;p=0.000 and p=0.000 respectively). Most optimal concentration was40% with the protective percentage equal to 71.8%.Conclusion: Pineapple fruit juice concentrations (20%, 40%, and 80%has an analgesic effect with the most optimal concentration of 40%.Keywords: analgesic, pain, pineapple fruit, writhing methodÂ Efek Analgesik Jus Buah Nanas Pada MencitÂ Latar Belakang: Nyeri adalah sensasi perangsangan sistem saraf yang dapat ditekan dengan pemberian zat analgetik. Penelitian sebelumnya menemukan bahwa nanas memiliki efek analgesik. Tujuan penelitian ini adalah untuk mengetahui efek analgesik nanas pada mencit.Metode: Efek analgesik diperiksa dengan menggunakan metode âwrithingâ pada 28 mencit jantan. Subyek penelitian dibagi menjadi 4 kelompok masing-masing 7 ekor. Kelompok kontrol menerima aquades dan kelompok lainnya menerima Â jus buah nanas secara oral dengan konsentrasiÂ 20%, 40% dan 80% dengan dosis 10 mL/kg/berat badan. Setelah 30 menit, asam asetat 3% disuntikkan intra peritoneal untuk menginduksi nyeri. Respons âwrithingâ diamati setiap 5 menit selama 30 menit.Hasil: Hasil rata-rata reaksi total âwrithingâadalah 2.39 Â± 0.40, 1.92 Â± 0.40, 1.50 Â± 2.13, 1.66 Â± 0.11 masing-masing untuk kelompok 1 sampai 4. Data ini menunjukkan penurunan yang signifikan dari jumlah respon âwrithingâ pada tikus dengan 20%, 40 % dan konsentrasi 80% dibandingkan dengan kelompok kontrol (p=0,023; p=0,000; dan p=0,000masing-masing). Konsentrasi optimal adalah 40% dengan persentase pelindung sebesar 71,8%.Simpulan: Konsentrasi Â jus buah nanas (20%, 40% dan 80%) memiliki efek analgesik dengan konsentrasi paling optimal pada 40%.Kata Kunci: analgesik, nyeri, nanas, writhingDOI: 10.15850/amj.v1n2.356